ANALISIS DOSIS PAPARAN RADIASI PADA INSTALASI RADIOLOGI DENTAL PANORAMIK - Candra Ancila; Eko Hidayanto (Youngster Physics Journal, 2016)
A research on the analysis of radiation dose exposure in panoramic dental radiology installations in Government General Hospital dr Kariadi Semarang, this study aims to identify and analyze the radiation dose received by workers and the general public and determine the effectiveness of radiation shielding in dental panoramic installations. Measurements were carrried out at the time of exposure using dental panoramic with surveymeter babyline. Measurements of doses exposure taken at the point operator station, waiting rooms and in the corridors employess and panoramic dental space, while measuring the effectiveness of radiation shielding in the door of the room and the operator station. Dose measurement result obtained in the operator station amounted 5,83 µSv/h, lounge area 2,4 µSv/h and at the corridor employees are not detected exposure dose when exposure using dental panoramic. For the effectiveness of radiation shielding door of the room is 12,24 % and in the operators station is 82,29 %. Can be concluded that the operator room and corridor employess fairly save from exposure to excessive radiation, while the lounge area has a value that approaches the dose limits. For radiation shielding door of the room is small and the effectiveness of the operator room is large.